2022
DOI: 10.3389/fcimb.2022.959903
|View full text |Cite
|
Sign up to set email alerts
|

Oral antibiotics perturbation on gut microbiota after prostate biopsy

Abstract: IntroductionThe use of antibiotics may induce the changes in gut microbiota. Previous studies have shown conflicting results on whether the changed gut microbiota by antibiotics can be recovered. Our study aims to investigate whether the gut microbiota could be recovered after a single dose of oral co-amoxiclav before transrectal ultrasound-guided transperineal prostate biopsy (TPPBx) in 5 weeks’ time.MethodsFifteen patients with elevated serum prostate-specific antigen (PSA) were recruited to provide pre-anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…68 Interestingly, research on single-dose antibiotic prophylaxis performed before transperineal biopsies showed that it could lead to changes in gut microbiota composition. 69 According to EAU guidelines, prostatic biopsy should be performed using a transperineal approach due to the lower risk of infective complications. Routine surgical disinfection of perineal skin should be performed.…”
Section: Prostate Biopsymentioning
confidence: 99%
See 1 more Smart Citation
“…68 Interestingly, research on single-dose antibiotic prophylaxis performed before transperineal biopsies showed that it could lead to changes in gut microbiota composition. 69 According to EAU guidelines, prostatic biopsy should be performed using a transperineal approach due to the lower risk of infective complications. Routine surgical disinfection of perineal skin should be performed.…”
Section: Prostate Biopsymentioning
confidence: 99%
“…Interestingly, research on single-dose antibiotic prophylaxis performed before transperineal biopsies showed that it could lead to changes in gut microbiota composition. 69…”
Section: Diagnostic Proceduresmentioning
confidence: 99%